Microfinance at the margin: Experimental evidence from Bosnia and Herzegovina - Britta Augsburg; Ralph de Haas; Heike Harmgart; Costas Meghir (Institute for Fiscal Studies (IFS), 2012)
We use an RCT to analyse the impact of microcredit on poverty reduction in Bosnia. The study population are loan applicants that would normally have just been rejected based on regular screening. We find that access to credit allowed borrowers to start and expand small-scale businesses. Households that already had a business and where the borrower had more education ran down their savings, presumably to complement the loan and to achieve the minimum amount necessary to expand their business. In less-educated households, however, consumption went down. A key new result is that there was a substantial increase in the labor supply of young adults (16-19 year olds). This was accompanied by a reduction in school attendance.
Keywords: O16; G21; D21; I32; 330; Microfinance; liquidity constraints; human capital; randomized controlled trial